(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2026)
Introduction: Base tongue carcinoma is commonly diagnosed an advanced stage in low-resource settings. Concurrent chemoradiotherapy (CCRT) and sequential chemoradiotherapy (SCRT) after induction chemotherapy are both used, but their comparative effectiveness remains unclear in such contexts. Aim of the study: The study aimed to compare the treatment response and acute toxicities between concurrent chemoradiotherapy and sequential chemoradiotherapy in patients with locally advanced base of tongue carcinoma in a limited-resource setting. Methods: The study was conducted using a purposive sampling technique at the National Institute of Cancer Research and Hospital (NICRH), Dhaka, over 12 months (June 2016–May 2017). A total of 60 patients with histopathologically confirmed squamous cell carcinoma of the base of tongue at stage III or IVA were enrolled and randomized into two equal groups. Arm A received concurrent chemoradiotherapy (CCRT) with external beam radiotherapy (66 Gy in 33 fractions over 6½ weeks) using the 3D Conformal Radiotherapy (3DCRT) technique, along with weekly cisplatin (40 mg/m²). Arm B received three cycles of induction chemotherapy (cisplatin 75 mg/m² on Day 1 and 5-FU 750 mg/m²/day for 3 days, every 3 weeks), followed by the same CCRT as Arm A. Data were analyzed using SPSS v22.0, employing descriptive statistics and Chi-square/Fisher’s exact tests, with p<0.05 considered statistically significant. Results: In this study involving 60 patients with unresectable locally advanced esophageal cancer, baseline characteristics such as tumor location (p=0.564), stage (p=0.558), and histological grade (p=0.739) were comparable between the concurrent and sequential CRT groups. The complete response rate was higher in the sequential CRT arm (56.7%) compared to the concurrent arm (46.7%), though this difference was not statistically significant (p=0.578). There were no significant differences in hematologic toxicity (e.g., anemia: p=0.793; leukopenia: p=0.630; neutropenia: p=0.278; thrombocytopenia: p=0.682) or non-hematologic toxicity (e.g., nausea/vomiting: p=0.907; mucositis: p=0.517; dysphagia: p=0.794; esophagitis: p=0.541; fatigue: p=0.898; anorexia: p=0.759) between the two treatment groups across follow-ups. These findings suggest that both concurrent and sequential CRT offer similar efficacy and safety profiles in the management of locally advanced esophageal cancer. Conclusion: Both concurrent and sequential chemoradiotherapy demonstrated comparable efficacy and tolerable toxicity profiles in treating locally advanced base of tongue carcinoma in a limited resource setting. Either approach can be considered a viable treatment option depending on patient factors and resource availability. J Bangladesh Coll Phys Surg 2026; 44: 26-32